Rumen Degradability and Small Intestinal Digestibility of the Amino Acids in Four Protein Supplements - Wang, Y. (Asian-Australas J Anim Sci, 2016)
The supplementation of livestock feed with animal protein is a present cause for public concern, and plant protein shortages have become increasingly prominent in China. This conflict may be resolved by fully utilizing currently available sources of plant protein. We estimated the rumen degradability and the small intestinal digestibility of the amino acids (AA) in rapeseed meal (RSM), soybean meal (SBM), sunflower seed meal (SFM) and sesame meal (SSM) using the mobile nylon bag method to determine the absorbable AA content of these protein supplements as a guide towards dietary formulations for the dairy industry. Overall, this study aimed to utilize protein supplements effectively to guide dietary formulations to increase milk yield and save plant protein resources. To this end, we studied four cows with a permanent rumen fistula and duodenal T-shape fistula in a 4×4 Latin square experimental design. The results showed that the total small intestine absorbable amino acids and small intestine absorbable essential amino acids were higher in the SBM (26.34% and 13.11% dry matter [DM], respectively) than in the SFM (13.97% and 6.89% DM, respectively). The small intestine absorbable Lys contents of the SFM, SSM, RSM and SBM were 0.86%, 0.88%, 1.43%, and 2.12% (DM basis), respectively, and the absorbable Met contents of these meals were 0.28%, 1.03%, 0.52%, and 0.47% (DM basis), respectively. Among the examined food sources, the milk protein score of the SBM (0.181) was highest followed by those of the RSM (0.136), SSM (0.108) and SFM (0.106). The absorbable amino acid contents of the protein supplements accurately reflected protein availability, which is an important indicator of the balance of feed formulation. Therefore, a database detailing the absorbable AA should be established.